“It’s where she belongs, isn’t it?” Lupe Vélez and Dolores del Río in Hollywood - Hernández-Rodríguez, R. (Nomadic New Women: Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century, 2024)
Mexican artistic influence at the beginning of the twentieth century was prevalent in America, most notably muralism, but also talent associated with the movies. This influenced the way Mexico was perceived in the United States, and by extension the way Lupe Vélez and Dolores del Río, the most successful Mexican actresses in early Hollywood, were appreciated. Both actresses had come to Hollywood to fulfill their dream of a career in the movies. At first, they were successful playing a variety of roles in silent movies, but once sound arrived, their accents made obvious their foreignness at a time when American culture was beginning to spread around the world and to establish its preeminence. They were aware of the challenges they faced and knew there was a price to pay if they wanted to continue in a business where the public decided, at a time when Americans distrusted foreigners. So, if that price was to overplay her earthy Mexicaness, in the case of Vélez, or emphasize her aristocratic image, in the case of del Río, they were ready to pay it. Mexico became the other par excellence in the early twentieth century, and these heavily accented actresses were evidence of that.
Keywords: Dolores del Río; Ethnic representation; Hollywood; Identity; Lupe Vélez; Mexican influence; Silent films; Stereotypes; Talkies; dept.wll

Reducing opportunity gaps and promoting enrollment through credit by examination for the Seal of Biliteracy - Gleason, Jesse; Latorre, Sobeira; Cardone, Resha (The Seal of Biliteracy in Higher Education, 2024)
This chapter explores the impact of implementing a partnership agreement to grant incoming university students credit based on their documented language proficiency. In 2018, an agreement was forged between an urban university and public school district, and, by extension, any high school offering the Seal of Biliteracy (SoBL) to offer students who hold the SoBL university credit for their language proficiency in a world language. This chapter examines the evolution of that agreement over a five-year period and its potential impact on students’ decision to pursue a minor/major in Spanish. Through semi-structured interviews, we also examined multiple university stakeholders’ perceptions and/or experiences about the value of the SoBL, the agreement to grant credit by examination (CBE), as well as other challenges, including the university’s reduction of their language requirement, transitions in leadership, and differing ideas about if and how best to award students credit based on examination.
Keywords: dept.wll

First language loss effect on bilingual autobiographical memory: examining memory phenomenology - Sorokina, A.N. (Applied Linguistics Review, 2024)
In the context of globalization and migration, individuals may experience language loss or first language (L1) attrition. While migrant language loss is well documented and researched, its impact on bilingual autobiographical memory remains underexplored. Existing research indicates that bilingual speakers encode memories in either their L1 or second language (L2), depending on the language context of the event. Language’s pivotal role in autobiographical memory has also been confirmed by bilingual psychotherapy research. This paper investigates whether L1 attrition can impair memories encoded in that language. Focusing on Russian-English speakers with various degrees of L1 attrition, this study examines the phenomenological characteristics of memories (vividness, emotional valence, accessibility, significance, and confidence in the event). Results from partial correlation and linear regression analyses demonstrated that language loss significantly compromises vividness and confidence, underscoring language’s integral function in maintaining bilingual autobiographical memory. © 2024 De Gruyter Mouton. All rights reserved.
Keywords: L1 attrition; bilingual autobiographical memory; dept.wll; memory phenomenology; peer-reviewed

Guest editorial: Language attrition – a comprehensive introduction - Schmitt, Elena; Sorokina, Anastasia (The Language Learning Journal, 2024)
Keywords: dept.wll

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed